Pembuatan Kokedama sebagai Pemanfaatan Limbah Sabut Kelapa di Pondok Pesantren Al Azhaar Tulungagung - Rohmatul Faizah; Chairunnisa Faza Nabilah; Dina Riska Triswanti; Lindu Lubuana H. S.; Diva Nuri Latifah; Vira Divka Fitriana (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
Kokedama is a technique of growing ornamental plants with a round shape. The KKNT Islamic Boarding School Innovation Group at the Al Azhaar Islamic Boarding School together with grade 1 and 2 students of SMA Al Azhaar made kokedama from coconut coir. The function of coconut coir as a planting medium is to be able to retain moisture in soil that dries quickly. This community service activity was carried out using two methods, namely (1) Socialization of Kokedama making from coconut coir, (2) Kokedama making training for Grade 1 and 2 students of SMA Al Azhaar Tulungagung. Kokedama training involves guidance in understanding the basic techniques of making kokedama and giving students the freedom to be creative. The training activity on making kokedama as a container for ornamental plants was carried out as a way to introduce innovations needed by high school students in grades 1 and 2 of Al-Azhaar High School in order to utilize leftover materials into useful materials.